Peran Pembelajaran Saintifik Dalam Meningkatkan Kemampuan Berpikir Kritis Anak Usia Dini - Vini Tenis; Meisye Haobenu; Maya Bani; Priska Oematan; Givendy Tnunay; Yeni Faitmoes; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Scientific learning is a learning approach that emphasizes the process of observing, asking, trying, reasoning, and communicating so that it can encourage children to think actively and critically from an early age. This study aims to determine the effect of scientific learning on the critical thinking skills of children aged 4-6 years at PAUD Hosana Sungkaen. This study uses a quantitative method with a research design using ex post facto. The research subjects were 20 children aged 4-6 years at PAUD Hosana Sungkaen. The data collection technique was carried out using a questionnaire compiled based on indicators of critical thinking skills of early childhood. The data obtained were analyzed using statistical tests to determine differences in critical thinking skills before and after the implementation of scientific learning. The results showed that there was a significant influence of scientific learning on the critical thinking skills of children aged 4-6 years by 20.7%, which means that the better the scientific approach, the more it can improve the critical thinking skills of early childhood.